Strategic human resource management in large enterprises: formation of personnel policy, structures, and internal regulations - Verbytska, Natalia (Global Prosperity, 2026)
Abstract. The article examines the transformation of personnel management systems in large enterprises through the lens of organizational design and the regulation of HR processes. It discusses the key operational models of the HR function – from traditional centralized structures to D. Ulrich’s business partner model and hybrid configurations with centers of expertise. This study examines whether formalizing HR policies and setting clear qualification standards actually improves organizational performance, and whether this varies by sector. We also look at how well HR teams coordinate with administrative and production units. We examine Google, Microsoft, and Amazon to see how HR structure affects day-to-day operations. The evidence points to a pattern: firms with clear internal rules and strategic HR priorities tend to be more productive, control costs better, and compete more effectively.